Effect of Application of Standard Operating Procedures on Employee Performance at PT. Mantap Sukses Cemerlang Medan - Juliana Juliana (Institute of Computer Science (IOCS), 2019)
This study aims to determine and analyze the effect of partial SOP (Standard Operating Procedure) implementation and its influence simultaneously on employee performance. This study was shown to determine the effect of the adoption of operational standard procedures on employee performance at PT. Mantap Sukses Cemerlang Medan. The application of SOP as an independent variable and employee performance as the dependent variable. The population in this study were all employees at PT. Mantap Sukses Cemerlang with a sample of 60 respondents. Data were collected using a questionnaire so the authors used saturated sampling by distributing the questionnaire directly. Then the data obtained and analyzed using the multiple linear regression equation is obtained by the equation Y = 12.812 + 0.466X1 + 0.159X2. This analysis includes a t test in the effect of the application of SOP on employee performance is 3,693 with Sig 0,000 and t test in the effect of product quality on purchasing decisions is 1,243 with Sig 0,001, R-Square of 0,456, f test of 7,477 with Sig 0,001.Implementation of Standard Operating Procedures